2009
DOI: 10.1007/s12325-009-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous prostaglandin E2 of cataract patients at trough ketorolac and bromfenac levels after 2 days dosing

Abstract: Ketorolac 0.4% maintained significantly higher aqueous concentrations and lowered aqueous PGE(2) levels significantly more than bromfenac 0.09% at trough levels. Ketorolac 0.4% administered q.i.d. may provide a more sustained control of intraocular inflammation and pain than bromfenac 0.09% administered b.i.d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Compared to diclofenac, it has been shown to provide significantly higher concentrations in the aqueous humour and to remain in the anterior chamber for a longer duration [20], which is the probable explanation for the extended mydriasis during cataract surgery [21]. It has also been shown to cause a stronger inhibition of PG synthesis compared to bromfenac [20,21]. Ketorolac is widely used in our country, especially for the prophylaxis of aphakia and pseudophakic cystoid macular oedema, ocular inflammation and pain, postoperative inflammation and allergic ocular conditions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to diclofenac, it has been shown to provide significantly higher concentrations in the aqueous humour and to remain in the anterior chamber for a longer duration [20], which is the probable explanation for the extended mydriasis during cataract surgery [21]. It has also been shown to cause a stronger inhibition of PG synthesis compared to bromfenac [20,21]. Ketorolac is widely used in our country, especially for the prophylaxis of aphakia and pseudophakic cystoid macular oedema, ocular inflammation and pain, postoperative inflammation and allergic ocular conditions [20].…”
Section: Discussionmentioning
confidence: 99%
“… 17 Concentrations achieved in this study are similar to those achieved at 6 h following intracameral administration. Topical dosing of ketorolac 0.40% at 6 h before surgery resulted in a considerably lower concentration of ketorolac in aqueous 18 compared with results achieved by intracameral dosing.…”
Section: Resultsmentioning
confidence: 84%
“…El-Harazi et al [ 27 ] also reported that no significant difference was detected in inflammatory response between groups given ketorolac 30 minutes before and 1 day after surgery. Bucci and Waterbury [ 28 ] studied patients undergoing cataract surgery who received either ketorolac q.i.d. or bromfenac b.i.d.…”
Section: Discussionmentioning
confidence: 99%